The Product Market Effects of Index Inclusion - Sharma, Varun (Review of Financial Studies, 2026)
Abstract I investigate how index membership affects firms’ product-market strategy. After plausibly exogenous index inclusion, firms gain market share by reducing product prices, giving better trade credit, and increasing sales and marketing expenses. Firms reduce prices for products with low market share and higher switching costs and habits. This comes at the cost of lower profitability, which increases in subsequent periods. Further analysis suggests that managerial learning about an improved funding environment from the post–index inclusion stock price increase is the underlying channel that leads to the observed increase in investment to gain market share. A model further corroborates these findings.